Multiple intelligences and student achievement in high school biology - Canzana, Efren E. (2007)
This study was conducted to investigate the effects of the Multiple Intelligence (MI) teaching approach on the achievement of high school students in Biology. The MI approach was utilized in teaching two units in Biology, namely, Biodiversity and Ecosystem. Quantitative research was used applying a randomized pretest-posttest control group design. The sample came from two Biology classes in a public school in Metro Manila. Based on the findings, it was concluded that there is a significant difference in the effects of the MI approach and the conventional approach, in favor of the former. Part of the conclusion of this study was a description of the MI approach to teaching biology as proposed (and tried out) by the researcher.
Thesis (M.A. Biology Education)--University of the Philippines, Diliman.
Keywords: Biology -- Study and teaching (Secondary) -- Philippines -- Manila Metropolitan Area; High school students -- Philippines -- Manila Metropolitan Area; Academic achievement -- Philippines -- Manila Metropolitan Area